PENGARUH TERMINAL HIGH ALTITUDE AREA DEFENSE (THAAD) TERHADAP HUBUNGAN DAGANG KOREA SELATAN-TIONGKOK - Putri, Ayu Sasqia; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to explain how the impact of the place THAAD (Terminal High Altitude Area Defense) in South Korea to the trade partnership South Korea and China at 2016-2017. THAAD (Terminal High Altitude Area Defense) placed in South Korea because South Korea terrified by the North Korea nuclear, but the placement of THAAD (Terminal High Altitude Area Defense) was opposed by China.This research uses a constructivism perspective by Alexander Wendt under of the book is Social Theory of Internastional Politics, which is then supported by nation-state analysis level. The methodology using a qualitatve method and collecting the data using a library research literature.This research shows that the impact caused by protesting China opposition for THAAD (Terminal High Altitude Area Defense) in South Korea, especially in Trade Partnership. China make a decision to boycott the products that belongs to South Korea. So in the field of export, opposition was make to the volume of export from South Korea to China continues to decrease, one of on exports of cosmetics. In the trade retail, cousing Lotte Group experienced significant losses due to a boycott from China and in a trade services, opposition to product K-Pop make the company’s stock of the entertainment industry has been decreased.Keyword: THAAD (Terminal High Altitude Area Defense), Trade Partnership, Boycott, Decrease.